Adsorption Thermodynamics, Kinetics and Mechanism of Calcium(II) Ions onto Kaolinite Clay in Coal Slime Water - Feng, L.; Tang, H.Y.; Liu, J.T.; Song, L.L. (Asian Journal of Chemistry, 2013)
Slime water is a highly concentrated micro-solid-liquid suspension-dispersion system which is mainly consisted of kaolinite and other clay minerals. The existence of these fine clay particles is one of the reasons why slimes water is difficult to clarify. In this work, the adsorption thermodynamics, kinetics and mechanism of Ca2+ onto kaolinite clay were systematically investigated through batch adsorption experiments, theoretical analysis, characterization of sorbents and field trial. The results show that the adsorption nature of Ca2+ onto kaolinite is spontaneous and exothermic. The adsorption data follow Langmuir isotherms. The possible adsorption mechanism is that CaOH+ in the system reacted with ºSiOH and > AlOH groups appeared in the surface of kaolinite. Sorption is mainly controlled by pseudo-second-order kinetics. The main advantages of calcium salt as coagulant are good selective, low-cost and high efficiency in precipitating kaolinite particles from slime water systems.